1980
DOI: 10.1136/bjo.64.10.766
|View full text |Cite
|
Sign up to set email alerts
|

Randomised double-blind trial of acyclovir and idoxuridine in dendritic corneal ulceration.

Abstract: Acyclovir has been shown to be superior to IDU in the treatment of experimental corneal infections with HSV in the rabbit'5 and has also shown promise in treating dendritic ulceration in man. In patients treated with minimal wipe debridement Jones et al. '6 showed that topical treatment with acyclovir prevented early recurrences in comparison with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…Asiklovir dendritik korneal keratitlerde etkin tedavi sağlamaktadır. 10 Kortikosteroidlerin epitelyal herpetik keratitlerde kullanılması kontrendikedir. 11 Ancak diskiform keratitlerin tedavisinde kortikosteroid kombinasyonuna ihtiyaç duyulmaktadır.…”
Section: Discussionunclassified
“…Asiklovir dendritik korneal keratitlerde etkin tedavi sağlamaktadır. 10 Kortikosteroidlerin epitelyal herpetik keratitlerde kullanılması kontrendikedir. 11 Ancak diskiform keratitlerin tedavisinde kortikosteroid kombinasyonuna ihtiyaç duyulmaktadır.…”
Section: Discussionunclassified
“…is sensitive to ACV: experimental (Schaeffer, 1978; in vitro. Pavan-Langston, 1978; animal) and clinical data (Collum, 1980) have shown that ACV has a greater therapeutic effect than I.D.U. even with I.D.U.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of new antivirals, particular Acyclovir [1] and BVDU [2], the outlook for herpetic keratitis has improved significantly. One of the manifestations of herpes simplex in the cornea is stromal, or disciform keratitis.…”
Section: Introductionmentioning
confidence: 99%
“…In a general way this is correct [1], but there are patients in whom Acyclovir is contraindicated. This paper describes the use of Acyclovir in patients with tear film disease and why it is desirable that these patients should be treated with systemic Acyclovir in dendritic corneal ulceration rather than local application of the drug.…”
Section: Introductionmentioning
confidence: 99%